2019
DOI: 10.1186/s40517-019-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature log simulations in high-enthalpy boreholes

Abstract: Temperature logs have important applications in the geothermal industry such as the estimation of the static formation temperature (SFT) and the characterization of fluid loss from a borehole. However, the temperature distribution of the wellbore relies on various factors such as wellbore flow conditions, fluid losses, well layout, heat transfer mechanics within the fluid as well as between the wellbore and the surrounding rock formation, etc. In this context, the numerical approach presented in this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…However, such numerical models (e.g. Espinosa-Paredes and Garcia-Gutierrez 2003;Espinosa-Paredes and Espinosa-Martínez 2009;Yang et al 2015;Wang et al 2019) require detailed information about the well (e.g. well geometry) and its drilling process (e.g.…”
Section: Existing Correction Methods For Log Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such numerical models (e.g. Espinosa-Paredes and Garcia-Gutierrez 2003;Espinosa-Paredes and Espinosa-Martínez 2009;Yang et al 2015;Wang et al 2019) require detailed information about the well (e.g. well geometry) and its drilling process (e.g.…”
Section: Existing Correction Methods For Log Temperaturesmentioning
confidence: 99%
“…mud flow rate, mud properties) to provide good results. However, especially in high-enthalpy regions, where the difference between measured temperature logs and true formation temperature can be very high due to occurring convection, numerical modelling which takes convection into account can deliver better corrected temperatures than analytical models (Wang et al 2019).…”
Section: Existing Correction Methods For Log Temperaturesmentioning
confidence: 99%
“…They suggested that the dimensionless time function by Kutun et al (2014) as given in equation ( 5) would be sufficiently accurate for engineering purposes for most values of flow time. This approach is frequently used in petroleum engineering as well as in geothermal reservoir (Nian et al, 2018;Song et al, 2018;Wang., 2019). In the following, we demonstrate its applicability in hydrology by performing numerical validation and also showing its field application.…”
Section: 2 Heat Transfer Modelmentioning
confidence: 99%
“…After exploration, a wide variety of methods can be exerted to model and simulate the hot underground reservoir. Temperature, pressure, flow regime, fracture network are known as the most important factors [14][15][16][17][18] .In the most simplified cases, a geothermal reservoir can be explored merely because of observable surface evidence such as hot springs. But, sophisticated exploration procedures are required to make a reliable prediction on the geothermal potential of a prospect.…”
mentioning
confidence: 99%
“…After exploration, a wide variety of methods can be exerted to model and simulate the hot underground reservoir. Temperature, pressure, flow regime, fracture network are known as the most important factors [14][15][16][17][18] .…”
mentioning
confidence: 99%